Exploring expectancy theory as motivation for learning French as a foreign language across gender - Hussin, Omrah Hassan @; Rahmat, Noor Hanim; Ismail, Saidah; Taib, Nor Azhar Mohd (Open Access Publishing Group, 2021)
Previously many language teachers feared that online learning may not give the same impact that it had for face-to-face learning. Nevertheless, now, online learning has become a new norm. More studies on online language learning have emerged. Past studies have shown that the success (or failure) of online classes is the strength of the engagement that took place during the online sessions. This study is done to see if there are gender differences in the learning of a foreign language; French; specifically in terms of Valence, instrumentality, expectancy. French as a foreign language across gender. The instrument used is a survey with four sections. Section A looks at the demographic profile, Section B looks at Valence, Section C looks at Instrumentality and Section D looks at Expectancy. A total of 170 learners responded to the survey. 44 of them were male learners, while 126 were female. Findings revealed variations in gender motivation and perceptions of online language learning. Article visualizations: